Subunit vaccines with a saponin-based adjuvant boost humoral and cellular immunity to MERS coronavirus - Chang, Chi-Chieh; Algaissi, Abdullah; Lai, Chia-Chun; Chang, Chun-Kai; Lin, Jr-Shiuan; Wang, Yi-Shiang; Chang, Bo-Hau; Chang, Yu-Chiuan; Chen, Wei-Ting; Fan, Yong-Qing; Peng, Bi‐Hung; Chao, Chih-Yu; et al. (Vaccine, 2023)
•MERS-CoV S1-Fd induces high levels of neutralizing activity as well as S1-specific IgG and isotypes.•MERS-CoV S1-Fd protects against MERS-CoV challenge and reduces viral loads in lung.•QS-21 but not AddaVax adjuvanted MERS-CoV S1-Fd activates long-term cellular immunity. Middle East respiratory syndrome coronavirus (MERS-CoV) outbreaks have constituted a public health issue with drastic mortality higher than 34%, necessitating the development of an effective vaccine. During MERS-CoV infection, the trimeric spike protein on the viral envelope is primarily responsible for attachment to host cellular receptor, dipeptidyl peptidase 4 (DPP4). With the goal of generating a protein-based prophylactic, we designed a subunit vaccine comprising the recombinant S1 protein with a trimerization motif (S1-Fd) and examined its immunogenicity and protective immune responses in combination with various adjuvants. We found that sera from immunized wild-type and human DPP4 transgenic mice contained S1-specific antibodies that can neutralize MERS-CoV infection in susceptible cells. Vaccination with S1-Fd protein in combination with a saponin-based QS-21 adjuvant provided long-term humoral as well as cellular immunity in mice. Our findings highlight the significance of the trimeric S1 protein in the development of MERS-CoV vaccines and offer a suitable adjuvant, QS-21, to induce robust and prolonged memory T cell response.